2015
DOI: 10.1161/atvbaha.115.305464
|View full text |Cite
|
Sign up to set email alerts
|

Interferons as Essential Modulators of Atherosclerosis

Abstract: Abstract-Interferons (IFNs) are key regulators of both innate and adaptive immune responses. The family of IFN cytokines can be divided into 3 main subtypes of which type I and type II IFNs are most well-defined. IFNs are known to be important mediators in atherosclerosis. Evidence from both in vitro and in vivo studies shows that the IFNs are generally proatherosclerotic. However, their role in atherosclerosis is complex, with distinct roles for these cytokines throughout different stages of the disease. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 110 publications
2
55
1
1
Order By: Relevance
“…This study clearly demonstrates that myeloid IFNgR2 is dispensable for both atherosclerosis development and its accompanying hepatic inflammation. So far IFNg was thought to be an essential pro-atherosclerotic cytokine [3,7]. But unlike several reports showing that targeting systemic IFNg or IFNg signaling strongly inhibits atherosclerosis development, we now demonstrate that focusing solely on myeloid IFNg signaling does not affect atherosclerosis [9e12,21].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This study clearly demonstrates that myeloid IFNgR2 is dispensable for both atherosclerosis development and its accompanying hepatic inflammation. So far IFNg was thought to be an essential pro-atherosclerotic cytokine [3,7]. But unlike several reports showing that targeting systemic IFNg or IFNg signaling strongly inhibits atherosclerosis development, we now demonstrate that focusing solely on myeloid IFNg signaling does not affect atherosclerosis [9e12,21].…”
Section: Discussioncontrasting
confidence: 60%
“…For many years now, IFNg and IFNg producing T cells are known to be present in the human atherosclerotic plaque [5,6]. This resulted in several IFNg-related atherosclerosis studies which have shown that IFNg is an essential atherogenic regulator throughout different stages of disease progression [7]. On the one hand, blockade or deletion of this cytokine or its receptor resulted among others in smaller and more stable lesions [8e12].…”
Section: Introductionmentioning
confidence: 99%
“…IFN-I also predicted therapy response, and interestingly, it had opposite predictive value for two targeted therapies. Patients with high IFN-I signature had a poor response to rituximab (106,107). Although RA patients with high IFN signature presented higher disease activity, in a recent study higher IFN score in neutrophils correlated with a good response to anti-TNF treatment (108,109).…”
Section: Rheumatoid Arthritismentioning
confidence: 94%
“…73 The resulting inflammatory microenvironment may also feedback to promote increased alteration of SMCs. Type I interferons, major players in atherosclerosis, 74 maintain SMC progenitors in an immature state, 75 suggesting that they might facilitate SMC transition to phagocytic macrophage-like cells.…”
Section: Innate Immune Functionsmentioning
confidence: 99%